Pelatihan E-Learning Menggunakan Office 365 Bagi Guru-Guru Sekolah Dasar Aisiyah Kasongan - Muhammad Fitriyanto (Universitas Pendidikan Indonesia, 2022)
Kasongan Aisiyah Elementary School is one of the private elementary schools in the province of Central Kalimantan. SD Aisiyah Kasongan is one of the private schools in the city of Kasongan which always updates learning by applying the latest technology. One of the technologies that want to be applied today is to operate Microsoft Office 365 as one of the media that will support the implementation of learning. The Community Service Team (PkM) from the Teaching and Education Faculty (FKIP) Muhammadiyah University of Palangka Raya (UMPR) has helped introduce and provide training on Microsoft Office 365 to SD Aisiyah Kasongan teachers. The results of this training are not only expected to provide additional knowledge but also to support the learning process at SD Aisiyah Kasongan